Analysis Need Guidance and Counseling Module Development For Bullying Prevention - Pristanti, Nindya Ayu; Rina Suryani; Yeni Marito; Abdul Munir; Armitasari (Coution: Journal Counseling and Education, 2025)
The analysis of module development needs in this research was the development of guidance and counseling modules which was carried out to find out how many students needed guidance and counseling modules to prevent bullying. This research is research and development (R&D) research. ADDIE is a development model used in this research including Analysis, Design, Development and Evaluation. The analysis stage is the stage of analyzing needs, curriculum and materials. The design stage involves designing the design and contents of the module. The development stage was carried out with limited trials and the implementation stage was carried out on 100 MAN 1 Medan students. The evaluation stage determines whether the modules and materials presented are suitable for use .